2021
DOI: 10.1016/j.heliyon.2021.e07949
|View full text |Cite
|
Sign up to set email alerts
|

Water footprint in gold extraction: A case-study in Suárez, Cauca, Colombia

Abstract: Assessment of water footprint of gold production in Su arez (Cauca, Colombia). Gray water footprint was found to be in the range of 272,125.39 to 404,825.11 m 3 per kg of gold extracted. The gold production had much larger gray water footprint than blue water footprint. Gold mining activity requires important management by environmental authorities and polluting agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Recently, a study on Hg in the trophic chain of Colombia has revealed important findings regarding the use of Hg during gold exploitation in different regions of this country [3], confirming what was previously disclosed by other authors, who reported that Colombia is one of the regions with the highest incidence of this dangerous metal in the world [4]. Therefore, in Colombia, Law 1658 from 2013 and the Minamata Agreement in 2018 were established, which propose the total elimination of the use of Hg in mining activities by 2018 and in various industrial activities by 2023 [5].…”
Section: Introductionsupporting
confidence: 83%
“…Recently, a study on Hg in the trophic chain of Colombia has revealed important findings regarding the use of Hg during gold exploitation in different regions of this country [3], confirming what was previously disclosed by other authors, who reported that Colombia is one of the regions with the highest incidence of this dangerous metal in the world [4]. Therefore, in Colombia, Law 1658 from 2013 and the Minamata Agreement in 2018 were established, which propose the total elimination of the use of Hg in mining activities by 2018 and in various industrial activities by 2023 [5].…”
Section: Introductionsupporting
confidence: 83%
“…We used the 2022 global datasets for species richness, threatened species and rarity (used in this study as proxy for endemic species) for amphibians, birds, mammals and reptiles. With mining operations known to demand substantial amounts of water, social conflict between mining and communities was also assessed in terms of rivalry over water resources (Alvarez‐Pugliese et al., 2021; Pardavé & Delvasto, 2017). We evaluated potential social conflict caused by the distribution of water resources based on hydrological balance data.…”
Section: Methodsmentioning
confidence: 99%
“…To provide some context, the blue water footprint, representing fresh water used in production, is about 80 m 3 /kg for gold production, equal to 1.5 years of an individual's water use in the United Kingdom (annual per capita water consumption 54 cubic meters 1 ). Furthermore, the grey water footprint for gold production, indicating the water needed to dilute pollutants, ranges from 272,000 to 404,000 m 3 /kg of gold extracted (Alvarez-Pugliese et al, 2021), equivalent to up to 7481 years of water use by an individual. These findings highlight the significant environmental implications associated with mining activities, particularly with regard to water resources.…”
Section: Introductionmentioning
confidence: 99%
“…The UCRB is recovering from long-term conflict. While rural populations struggle with social inequalities, including lack of access to basic sanitation, violence, dispossession, and oppression (Arbeláez-Ruiz, 2021), the catchment has been degraded by various competing human activities, including widespread extractive processes such as legal/illegal mining (Alvarez-Pugliese et al, 2021;Gallo Corredor et al, 2021;Rochlin, 2021), logging (González-González et al, 2021), monocultures (Correa-García et al, 2018), and those associated with illegal activities such as coca leaf production (Thomson et al, 2022). Vélez Torres and Vélez Galeano (2019) reviewed historical environmental conflicts in the UCRB.…”
mentioning
confidence: 99%